TUBERCULOSE EM IDOSOS NO MARANHÃO: contribuição para o programa de controle. - SILVA, Leticia Ferreira da (2017)
Tuberculosis (TB) is considered to be a public health problem because of its high incidence, prevalence, and more frequent involvement of populations living in precarious socioeconomic conditions, especially in developing countries. Following the worldwide trend of population aging, the incidence of TB in Brazil begins to reach the elderly. In Brazil, in 2012, 71,230 new TB cases were registered, and 9.7% occurred in the elderly, a fact that reveals the epidemiological importance of the disease in this age group. The objective was to analyze the profile and identify the factors associated with TB in the elderly in Maranhão from 2010 to 2015. An analytical cross - sectional study was carried out with the cases of TB in the elderly in the State of Maranhão. The information was collected from the database of the Notification of Injury Information System (SINAN) of the State Secretariat of Health of the State. To identify the associations between the outcome (tuberculosis in the elderly) and the independent variables, the Poisson regression was used, with robust adjustment of the variance. Prevalence ratios (PR) and 95% confidence intervals (95% CI) were estimated. In the unadjusted analysis, the age of schooling was ˂8 years (RP = 3.58, 95% CI = 3.04-4.22, p≤0.001), pulmonary clinical form (RP = 1) , 95% CI = 1.10-1.63, p = 0.003), anti-HIV test (RP = 1.67, 95% CI = 1.50-1.84, p≤0.001), and having diabetes (RP = 2.71, 95% CI = 3.38-3.09, p≤0.001). After adjustment of the model, only schooling ˂8 years of study (PR = 3.43, C95% = 2.92-4.02, p≤0.001), closure for not cure (PR = 1.20, 95% CI, (PR = 1.37, 95% CI = 1.26-1.49, p≤0.001) and to have diabetes (PR = 2, 24, 95% CI 2.03-2.47, p≤0.001) presented as a factor that increases the chance of the occurrence of tuberculosis in the elderly. The other variables were: male gender (RP = 0.86, 95% CI = 0.79-0.93, p≤0.001), non-white race / color (RP = 0.77, 95% CI = 0.69-0.86, p≤0.001), retreatment entry (PR = 0.74, CI% 95 = 0.63-0.86, p≤0.001), anti-HIV positive test (PR = 0.24 , 95% CI = 0.08-0.73, p = 0.012), had no supervised treatment (PR = 0.87, 95% CI = 0.80-0.94, p = 0.002), had comorbidity alcoholism (PR = 0.53, 95% CI = 0.42-0.66, p≤0.001) and mental illness (PR = 0.47, 95% CI = 0.31-0.73, p≤0.001). There was a high prevalence of TB in the elderly in the State. The degree of schooling ˂8 years of study, closure due to non-cure, unrecovered HIV test and having diabetes increase the chance of the elderly developing tuberculosis. There is a need to adopt strategies to accompany this clientele, seeking to reduce this prevalence rate.